Marketing Capability and Export Performance: the Moderating Effect of Export Dependence - Tooksoon, Phadett; Mohamad, Osman (UI Scholars Hub, 2010)
This research examines the relationship between marketing capability and export performance and the moderating effect of export dependence. The marketing capability of Thai agro-based exporting firms can be classified into four dimensions, namely product capability, distribution capability, price capability, and promotion capability. Among the four dimensions of marketing capability, only price capability and promotion capability are significantly and positively related to export performance. Export dependence moderates the relationship between distribution capability as well as price capability with export performance. Firms with high export dependence register higher export performance when marketing capability in term of distribution capability is high. Similarly, firms with high export dependence register higher export performances when marketing capability in term of price capability is high.